(untitled) (Global Journal of Management and Business Research, 2025)
This paper is an attempt to investigate whether working capital management influences the financial performance of the sample companies or not In order to achieve this objective the researchers have taken into consideration seven sectorial indices and each sectorial index is represented by ten companies The research is based on a reference period of fifteen years ranging from 2006 to 2020 The researchers have taken Return on Capital Employed ROCE and Return on Net Worth RONW as proxy to financial performance After the thorough analysis the overall findings put forth by the study confirm that working capital management has statistically significant impact on the financial performance of the sample companies The findings presented by the study affirm that Average Receivable Period ARP and Average Payable Period APP positively impact the financial performance of the sample firms statistically in a significant manner However on the other hand the results also affirm that Inventory Conversion Period ICP and Cash Conversion Cycle CCC negatively impact the financial performance of the sample firms statistically in a significant manner